The Usefulness of Fluorescence Imaging in Laparoscopic Liver Resection - Chalokool, Vachiraluck; Taesombat, Wipusit (Digestive Disease Interventions, 2024)
Indocyanine green (ICG) has been used extensively in medical applications after being approved by the Food and Drug Administration (FDA) in 1954. In the beginning, this substance was originally employed for evaluating cardiac output and quantifying liver function. The widespread acceptance of the technique was delayed until the early 2000s, when advancements in digital imaging resolution provided more satisfactory images compared with those of film-based photography. ICG-based fluorescence imaging has since been used in various aspects of liver surgery. In 2008, Aoki et al first reported an intraoperative technique for subsegmental and segmental fluorescent staining during open hepatectomy, achieving a success rate of 93% in identifying the anatomical plane. At about the same time, laparoscopic liver resections (LLRs) were increasingly used for liver malignancies but were still in a developmental phase with yet to be standardized surgical protocols. Combined ICG fluorescence imaging in LLR has since been developed to improve the quality and precision of anatomical liver resections. This article is a case presentation and review of the clinical applications of ICG fluorescence imaging in liver surgery.
Keywords: ICG; laparoscopic liver resection; fluorescence image